Methionine-enkephalin-treatment suppresses the pituitary-ovary axis in the cichlid fish Oreochromis mossambicus - C.B. Ganesh; Vijayalaxmi (Aquaculture Reports, 2020)
The involvement of endogenous opioid peptides in regulation of reproductive activity is implicated in a majority of vertebrates. Methionine-enkephalin (M-ENK) is an endogenous opioid peptide neurotransmitter produced in the central nervous system. Although a role for M-ENK in antinociception (pain suppression) and mediation of stress has been suggested, its influence on fish reproduction is not clearly understood. The aim of the present investigation was to determine the role of M-ENK on the reproductive-axis of the female tilapia Oreochromis mossambicus. Treatment of stripped O. mossambicus with 300 μg M-ENK during the ovarian cycle resulted in suppression of luteinizing hormone (LH) secretory activity. This was evidenced by a significant reduction in the area and the intensity of LH immunoreactivity in the proximal pars distalis of the pituitary gland as compared to controls during the prespawning phase. At the ovarian level, the treatment of M-ENK caused a significant increase in the mean number of follicles with chromatin nucleolar (stage I), perinucleolar (stage II) and cortical alveolar stages (Stage III). Although the mean number of early vitellogenic follicles (stage IV) did not significantly differ from that of initial controls and controls, the mean number of late vitellogenic follicles (stage V, preovulatory) and the serum levels of estradiol were significantly lower in M-ENK treated fish compared to those of controls. However, there was a significant increase in the serum levels of cortisol in M-ENK treated fish compared to controls. Together, these results suggest that treatment of M-ENK inhibits the recruitment of follicles at late vitellogenic stage through the suppression of steroidogenesis in the ovary and LH secretory activity at the level of the pituitary gland in fish. Besides, the ability of M-ENK to stimulate serum cortisol levels indicates a role for this peptide in regulation of the hypothalamo-pituitary-interrenal axis in fish.